A seasonal study on the role of h'F/meridional winds in influencing the development of ESF irregularities over Indian sector - Sreekumar, Sreeba; Sripathi, S. (My University, 2017)
In this paper, we present the seasonal variation of nighttime thermospheric meridional winds over Hyderabad as derived using dual ionosonde observations located at Tirunelveli (8.7 N, 77.7 E, Dip Lat = 0.3 N), an equatorial station and Hyderabad (17.38 N, 78.45 E, Dip Lat = 12 N), a low latitude station, respectively, over the period of April-December 2013 using h’F data as discussed in (Sreekumar and Sripathi, 2016). The calculated winds has been compared with HWM14 wind model. The results show that trends of the derived winds from the ionosonde h’F data matches well with model wind near to midnight hours in all the seasons. However, some dissimilarities were observed during early night hours. Especially, the poleward winds during early night hours for different seasons were not well reproduced by the model. Later, the study is extended to understand the role of meridional winds in causing the variability of ESF occurrence vis a vis h’F. The histogram analysis of h’F vs wind values just before ESF onset reveals that the most probable combination of wind and h’F on the ESF days are centered around 350 km and 50 m/s. Additionally, we also performed Superposed Epoch Analysis (SEA) based on longer and shorter duration ESF events. The analysis reveals the distinct differences in the longer and shorter duration ESF events of Summer and Autumn equinox where the values of h’F as well as meridional winds where such that a steep change in reduction of poleward winds prior to ESF onset supported the longer duration ESF events in both seasons. However, this steep reduction is not so significant for the shorter duration ESF events indicating that meridional winds could play a crucial role in extending the spread F durations in longer duration events. The observations clearly demonstrate the reduction of poleward wind velocities during vernal equinox as compared to Autumn equinox, where larger poleward winds were present around ESF onset times. These observations are consistent with the equinoctial asymmetry as seen during year 2013 where more number of ESF occurrences were observed during vernal equinox as compared to Autumn equinox. Additionally on seasonal basis, analysis of the significance of meridional wind magnitudes during scintillation and non scintillation days were performed. The result suggests that non scintillation days were characterized with larger poleward wind magnitudes than scintillation days during vernal equinox and summer season. However, such a trend was not seen in the Autumn equinox season. This might indicate the possible role of poleward meridional wind in reducing the number of scintillation occurences during this season in addition to weakening of PRE height.
Keywords: ESF irregularities; Meridional winds and h'F; Indian sector